Age-specific sequence of colorectal cancer screening options in Germany: A model-based critical evaluation - Heisser, Thomas; Weigl, Korbinian; Hoffmeister, Michael; Brenner, Hermann (PLoS medicine, 2020)
Background The current organized screening program for colorectal cancer in Germany offers both sexes 5 annual fecal immunochemical tests (FITs) between ages 50 and 54 years, followed by a first screening colonoscopy at age 55 years if all of these FITs were negative. We sought to assess the implications of this approach for key parameters of diagnostic performance. Methods and findings Using a multistate Markov model, we estimated the expected detection rates of advanced neoplasms (advanced adenomas and cancers) and number needed to scope (NNS) to detect 1 advanced neoplasm at a first screening colonoscopy conducted at age 55 after 5 preceding negative FITs and compared them with the corresponding estimates for a first screening colonoscopy at age 55 with no preceding FIT testing. In individuals with 5 consecutive negative FITs undergoing screening colonoscopy at age 55, expected colonoscopy detection rate (NNS) was 3.7% (27) and 0.10% (1,021) for any advanced neoplasm and cancer, respectively, in men, and 2.1% (47) and 0.05% (1,880) for any advanced neoplasm and cancer, respectively, in women. These NNS values for detecting 1 advanced neoplasm are approximately 3-fold higher, and the NNS values for detecting 1 cancer are approximately 8-fold higher, than those for a first screening colonoscopy at age 55 without prior FITs. This study is limited by model simplifying assumptions and uncertainties related to input parameters. Conclusions Screening colonoscopy at age 55 after 5 consecutive negative FITs at ages 50-54, as currently offered in the German cancer early detection program, is expected to have very low positive predictive value. Our results may inform efforts to enhance the design of screening programs.
Gesehen am 21.09.2020